2022
DOI: 10.1155/2022/2635375
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Network Pharmacology and Clinical Study to Reveal the Effects and Mechanisms of Bushen Huoxue Huatan Decoction on Polycystic Ovary Syndrome

Abstract: Objective. Bushen Huoxue Huatan Decoction (BHHD) is a classic prescription for treating polycystic ovary syndrome (PCOS). This study aims to explore the effects and possible mechanisms of BHHD on PCOS by integrating network pharmacology and clinical study. Methods. The components and potential drug targets of BHHD were analysed using the TCMSP platform, and the potential pathogenesis targets for PCOS were analysed using the GeneCards and OMIM databases. Subsequently, a disease-compound-target network diagram w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In recent years, traditional Chinese drugs have enriched the development of therapy for uterus-related diseases. Ding et al revealed that as a classic traditional prescription, Bushen Huoxue Huatan decoction improved polycystic ovary syndrome through regulating hormones, reversing insulin resistance, and alleviating inflammation reactions, resulting in fertility improvement [ 21 ]. Feng et al also proved that Bushen Huoxue decoction was effective in the treatment of unexplained recurrent spontaneous abortion via activation of the PI3K/AKT pathway [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, traditional Chinese drugs have enriched the development of therapy for uterus-related diseases. Ding et al revealed that as a classic traditional prescription, Bushen Huoxue Huatan decoction improved polycystic ovary syndrome through regulating hormones, reversing insulin resistance, and alleviating inflammation reactions, resulting in fertility improvement [ 21 ]. Feng et al also proved that Bushen Huoxue decoction was effective in the treatment of unexplained recurrent spontaneous abortion via activation of the PI3K/AKT pathway [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…And this study inferred that BUSHEN HUOXUE HUATAN decoction has potential therapeutic effects on PCOS, and the mechanism could be related to regulating hormone levels, improving IR, reducing inflammation, and promoting pregnancy. QUR may be an important active ingredient (Ding et al, 2022). There are similar studies, for example, YIJING decoction treatment for PCOS patients, which also considered QUR as one of the potentially effective components (Lin et al, 2022).…”
Section: Effects Of Qur Tcm Compound On Pcosmentioning
confidence: 97%
“…BUSHEN HUOXUE HUATAN decoction is also a classic prescription for treating PCOS (Ding et al, 2022). There was a non-randomized controlled study that enrolled 62 patients with PCOS and IR, and all patients received BUSHEN HUOXUE HUATAN decoction for 3 months.…”
Section: Effects Of Qur Tcm Compound On Pcosmentioning
confidence: 99%
“…Current treatment strategies for PCOS mainly include oral medications (short-acting combination oral contraceptives, progestins, insulin sensitizers, and ovulation induction), in vitro fertilization-embryo transfer, and surgery. However, long-term clinical practice suggests that the above-mentioned strategies have certain limitations, for example, high recurrence rates and invasiveness, unsatisfactory long-term results, and various side effects [ 3 ]. Recently, alternative therapies have been gradually coming into focus as a more favorable option for PCOS treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%